2006
DOI: 10.1590/s0074-02762006000200011
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus screening in contacts of blood donors with antibodies against core protein (anti-HBc), but without surface antigen (HBsAg)

Abstract: To increase blood safety Brazil introduced screening for anti-HBc among blood donors in 1993. There was a decrease in the hepatitis B virus (HBV) transmission, but this measure identified a great number of HBsAg-negative, anti-HBc-positive Studies have shown an increasing chance of finding HBV-positive subjects among household contacts of hepatitis B virus (HBV) carriers as compared with contacts of HBV-negative individuals (Berris et al. 1973, Kashiwagi et al. 1984, Milas et al. 2000. HBV spread inside fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Likewise, the low prevalence of HBV infection is in accordance with the low prevalence of HIV, since our patients are exposed to sexual (but not parenteral) risks, as well as with the declining rates of HBV circulating in Brazil previously reported [56][57][58]. The fact that a high proportion of women in this study had already been tested for HIV is the result of both CETAD's Harm Reduction Program and the enrollment of these women in previous research projects.…”
Section: Discussionsupporting
confidence: 87%
“…Likewise, the low prevalence of HBV infection is in accordance with the low prevalence of HIV, since our patients are exposed to sexual (but not parenteral) risks, as well as with the declining rates of HBV circulating in Brazil previously reported [56][57][58]. The fact that a high proportion of women in this study had already been tested for HIV is the result of both CETAD's Harm Reduction Program and the enrollment of these women in previous research projects.…”
Section: Discussionsupporting
confidence: 87%
“…Individuals positive for either are disqualified because of ongoing or past infections. In Brazil, screening for anti‐HBc among blood donors was introduced in 1993, which resulted in decrease of HBV transmission (Fortes et al , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In the Mid-West region, studies carried out in Goias have demonstrated the prevalence for HBV infection markers, ranging from 6.1% in the female urban population (4) to 63.4% in renal chronic patients (5) . In Mato Grosso, a 31% index has been found in a rural community (6) and 37.1% in those that had contact with blood donors positive for HBsAg (7) . In Mato Grosso do Sul, studies carried out in Campo Grande pointed out 9.4% indexes in blood donors (8) , 19.8% in Afro descendents (9) and 10.8% in dentists (10) .…”
Section: Introductionmentioning
confidence: 99%